2018
DOI: 10.1038/s41598-018-32198-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Adaptation of the Yellow Fever Virus to the Mosquito Aedes albopictus and Potential risk of urban epidemics in Brazil, South America

Abstract: Despite the availability of an efficient vaccine, Yellow fever (YF), a viral disease transmitted by mosquitoes, is still a threat. In Brazil, the yellow fever virus (YFV) has been restricted to a jungle cycle for more than 70 years. However, YFV has recently invaded populated cities in the Southeast such as Rio de Janeiro where the opportunistic mosquito Aedes albopictus is well established. Using in vivo passages of YFV in Ae. albopictus, we have selected viral strains presenting substitutions in NS1 gene. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 35 publications
(38 reference statements)
0
28
0
5
Order By: Relevance
“…In Asia and Oceania, the potential for inter-species transmission of JEV and RRV must be evaluated. It is important to take into account that the risk of arbovirus emergence is dynamic and in continuous evolution because mosquito populations, virus genetics, and the possibility of their contact varies according to time and place, and adaptations could be expected, particularly for invasive pathogens and vectors [186]. For instance, in the Indian Ocean region, the interaction between Ae.…”
Section: Discussionmentioning
confidence: 99%
“…In Asia and Oceania, the potential for inter-species transmission of JEV and RRV must be evaluated. It is important to take into account that the risk of arbovirus emergence is dynamic and in continuous evolution because mosquito populations, virus genetics, and the possibility of their contact varies according to time and place, and adaptations could be expected, particularly for invasive pathogens and vectors [186]. For instance, in the Indian Ocean region, the interaction between Ae.…”
Section: Discussionmentioning
confidence: 99%
“…albopictus has only been a bystander and its role as a vector outside laboratory settings has not been demonstrated. Amraoui et al (2016Amraoui et al ( , 2018 and Couto-Lima et al (2017), independently infected Ae. albopictus with YFV and showed that the virus was detected in the saliva from day 14th post-exposure.…”
Section: Aedes Albopictusmentioning
confidence: 99%
“…Hematophagous female mosquitoes belonging to the genera Aedes, Anopheles, and Culex can transmit disabling and deadly diseases. They infect humans with protozoan parasites causing malaria, oestridean parasites causing myasis, filarioidean parasites causing helminthiasis and viruses causing Dengue fever, Chikungunya, Japanese encephalitis, Sindbis fever, Rift Valley fever, West Nile fever, Yellow fever, and Zika (Amraoui et al, 2018). Mosquito-borne diseases outbreaks have soared over the last decades, exemplified by the 30 fold increase of Dengue fever over the last 30 years World Health Organization (WHO, 2015).…”
Section: Introductionmentioning
confidence: 99%